LINC02688 and PP7080 as novel biomarkers in early diagnosis of gastric cancer - Sadegh Fattahi; Novin Nikbakhsh; Hassan Taheri; Elham Ghadami; Mohammad Ranaee; Haleh Akhavan-Niaki (Non-coding RNA Research, 2021)
Despite considerable progress in gastric cancer screening, prevention, and treatment, it remains a major cause of morbidity and mortality worldwide. Due to late diagnosis of the disease, early potential diagnostic biomarkers are needed. Accumulating evidence indicates that non-coding RNAs have potential applications as diagnostic and prognostic biomarkers in gastric cancer. Herein, we investigated the expression levels of two novel non-coding RNAs, long intergenic non-protein coding RNA 2688 (LINC02688) and LOC25845 (PP7080) by real-time PCR for the first time in 47 gastric cancer patients. We found significant downregulation of LINC02688 and LOC25845 (PP7080) with 3.44 and 2.2-fold decrease, respectively in tumoral tissues in comparison with their adjacent non-tumoral counterparts (P < 0.0001). Our data also indicates that more than 96% and 88% of patients showed unchanged or decreased expression of LINC02688 and LOC25845 (PP7080), respectively. As most gastric cancer patients showed lower expression of these two lncRNAs, no significant association between clinicopathological features of the patients and the level of LINC02688 and LOC25845 (PP7080) expression could be detected. Furthermore, ROC curve analysis indicated that LINC02688 and PP7080 can serve as good predictive biomarkers for distinguishing tumoral tissues from their adjacent non-tumoral counterparts. Taken together, our findings suggested that these two novel tumor suppressor non-coding RNAs may act as novel diagnostic biomarkers for diagnosis of carcinogenesis event even at earlier stages of gastric adenocarcinoma.